AUTHENTICITY FOR GRAPHIC DESIGNER - Fuat AKDENİZLİ (Fırat University, 2019)
The traces of authenticity have been observed in the field of art since antiquity. It is known that antique ceramic artists have named their works by writing their names on them. Similarly, renaissance artists have increased their personal recognition by signing their works. With the names and the signatures written on the artistic work, not only the work of art but also the artist's' himself have gained individuality and authenticity. In this context, one can talk about two kinds of authenticity, one is related to the work of art and the other is related to artist's' himself. In the field of graphic design, the situation is more complicated. Graphic designers often do not sign their works. The work of design is not unique, there are many copies. The name of the graphic designer is almost invisible. The inability of the graphic designer's existence as an authentic personality in the market creates a feeling of worthlessness. The working conditions that prevented the graphic designer from being authentic can be traced back to the beginning of Industrial Revolution age. The visibility of the artists started to increase with "Arts and Crafts”, and then continued with "First Things First" and "Do It Yourself”, which can be interpreted as efforts to ensure authenticity for graphic designers. In this article, the social position of the graphic designer as an individual was centered rather than the authenticity of his works. The contradiction between the expectations of today's graphic designer and the market conditions will be explained in a historical order and with its reasons. Within the social context, the possibilities of developing an authentic attitude for the graphic designer will be questioned in terms of Berman's definition. The steps that can be taken to develop an authentic identity will be discussed through the examples of designers and their explanations on this subject. This article is intended to provide a perspective on graphic designers' authenticity and to provide a source for researchers working on the field.